2017
DOI: 10.4238/gmr16029660
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the clone by harvest interaction in the selection of sugarcane genotypes in a regionalized program

Abstract: ABSTRACT. The recommendation of sugarcane clones depends on several factors, as the response or performance of the clones over different cuts or harvests. The clone by harvest interaction might be difficult to identify superior clones in the final stages of the sugarcane breeding program. Thus, the objective of this study was to investigate and describe the implications of the genotype by harvest interaction in the adaptability and stability of genotypes and delineation of mega-environments from a set of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Further research is needed to strengthen the recommendations for the promising clones included in this work; high and stable yields have been attained in PC and RC-1. Cabral et al (2017) suggested assessing the genotypes in several cuts or harvests, despite high results and stability in diverse environments. Varieties with early maturity, very tolerant of drought, accompanied by high cane and sugar yields, provide options for early planting in Indonesia.…”
Section: Kg)mentioning
confidence: 99%
“…Further research is needed to strengthen the recommendations for the promising clones included in this work; high and stable yields have been attained in PC and RC-1. Cabral et al (2017) suggested assessing the genotypes in several cuts or harvests, despite high results and stability in diverse environments. Varieties with early maturity, very tolerant of drought, accompanied by high cane and sugar yields, provide options for early planting in Indonesia.…”
Section: Kg)mentioning
confidence: 99%
“…This fact is possibly related to the genetic aspects of the cultivars and the interactions of the genotypes with the environment in which they are inserted (Silva et al, 2017c). Inherent factors such as sprouting, cane-age, and root activity may affect productivity decrease (Manhães et al, 2015;Cabral et al, 2017). In addition to environmental attributes such as luminosity, availability of water and mineral nutrients that can negatively influence sugarcane yield (Silva et al, 2017a).…”
Section: Natural Biomass Productivity Of the Sugarcane Areamentioning
confidence: 99%
“…This ETc was comparable to the mean ETc in two seasons computed by [21,22], ranging from 1399 mm/year (0% water deficit) and 1160 mm (30% water deficit) in the semiarid region. Annual sugarcane evapotranspiration was in the ranges of 1023.9 -1068.5 mm in Brazil [23], 1231.5 mm average from nine seasons [24], 1645 mm [25], 829 mm (PC), and 685 mm (RC) in Southeast Brazil [11]. The other related researches also informed 1369.84 mm in Myanmar [26], 1450 mm in Bundaberg, Australia [13], 1100-1960 mm in many sites in Australia [19], 1542-1964 mm in Hawaii [27].…”
Section: Introductionmentioning
confidence: 99%